Estado nutricional y su relación con la obesidad e hipertensión en pacientes de 45 - 64 años de edad en la Parroquia Roberto Astudillo del cantón Milagro durante el periodo junio - octubre 2023. - Muñoz Aguirre, Erick Eduardo (2023)
This research project was conducted in order to determine the relationship between nutritional status and obesity and hypertension in patients aged 45 - 64 years in the parish "Roberto Astudillo" in the canton of Milagro. Thus, arterial hypertension, by its acronym, HTA, and obesity, strongly affect the individual, with the limitations that these diseases present at the time of suffering them. The method used in this study was inductive and deductive, allowing the analysis of the data obtained through anthropometric assessment and the evaluation of HT with blood pressure monitors. In addition, a survey was applied as support material to highlight food consumption. It was concluded that arterial hypertension and obesity affect the organism in such a way that the BMI or body mass index increases, leading to the development of other metabolic diseases.